Bedside Monitor Based on Personal Computer Using STM32F7 Microcontroller - Ingga Ariestya Riswandhani; Priyambada Cahya Nugraha; Syaifudin Syaifudin (Jurnal Teknokes, 2023)
A vital sign examination is one of the important indications used to establish the diagnosis of a disease and is useful for determining the medical treatment plan needed for the patient. An electrocardiograph (ECG) is a parameter in medical equipment used in the process of measuring the electrical activity of the heart muscle by measuring biopotential differences from the body surface. In 2016, cardiovascular disease was the number-one cause of death in the world. This happens because the detection of cardiovascular disease is often late, so a monitoring tool is needed that can monitor the patient's condition quickly and efficiently. The purpose of this research is to create a tool that is used to facilitate the monitoring of patient conditions. The implication of this research is that in the many cases where the signal produced is not perfect and there is still a lot of noise, this can be overcome by using the STM32F7 microcontroller, which has a 16-bit resolution, so that the resulting signal will be better, smoother, and have less noise. produced is very small. The method used in this study was to use a phantom ECG as a comparison and to use five respondents whose BPM values were to be compared with another comparison using a pulse oximeter. The design of this tool uses an ECG analog circuit that is placed on the patient's lead II leads to detect the patient's electrocardiograph signal. Data processing will be done using the STM32F7 microcontroller, and the results of the data processing will be sent to the PC using Visual Basic. The results showed that the BPM error value using a phantom ECG was 2.5%. While the smallest error value is 0,83%. In BPM measurements using 5 respondents, the largest error value was 0.9% and the smallest error value was 0%. The results of these tests indicate that this module can be used to monitor the value of each parameter in accordance with the plan.